SPECIFIC ASPECTS OF TEACHING THE UZBEKI LANGUAGE FOR THE CHINESE - Iskandarova Gulbahor Turabaevna; Shirinova Ekaterina Turakulovna; Mirzaahmedova Dilsora (Western European Studies, 2024)
The article talks about the specific phonetic, lexical, orthoepic and grammatical features of teaching Uzbek as a foreign language to the Chinese. In language teaching, comments are made about the linguistic and cultural characteristics of both languages
Keywords: Uzbek language as a foreign language; phonetic